2020
DOI: 10.1111/ijd.15188
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of noncultured hair follicle cell suspension and noncultured epidermal cell suspension in repigmentation of leukotrichia and skin patch in vitiligo: a randomized trial

Abstract: Background Vitiligo manifests as hypo-to de-pigmented macules, which are sometimes associated with leukotrichia. For complete cosmetic improvement, the repigmentation of leukotrichia is an important component. Methods This randomized controlled trial included patients with stable vitiligo with leukotrichia. Two vitiligo patches in each patient were randomized to receive either of the two procedures. The patients were followed up for 9 months posttransplantation. The efficacy of hair follicle cell suspension (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Consistent with the findings of Gunaabalaji et al who compared both methods in the treatment of leukotrichia, the total cell yield in ECS was eight times higher than HFCS in the present study 13 . However, the authors reported similar proportions of HMB45+ melanocytes in both cell suspensions 13 . Contrarily, in the present study, higher and significant total cell yield and HMB‐45+ melanocytes were observed with ECS.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of Gunaabalaji et al who compared both methods in the treatment of leukotrichia, the total cell yield in ECS was eight times higher than HFCS in the present study 13 . However, the authors reported similar proportions of HMB45+ melanocytes in both cell suspensions 13 . Contrarily, in the present study, higher and significant total cell yield and HMB‐45+ melanocytes were observed with ECS.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective monocentric study showed that the melanocyte–keratinocyte transplantation procedure is a good alternative for achieving a high rate of repigmentation in patients with limited stable vitiligo 30 . In addition, non‐cultured epidermal cellular grafts were shown to be better than hair follicle grafts in repigmentation of leukotrichia and vitiligo, although the difference was not statistically significant 31 …”
Section: Surgical Treatmentmentioning
confidence: 99%
“…30 In addition, non-cultured epidermal cellular grafts were shown to be better than hair follicle grafts in repigmentation of leukotrichia and vitiligo, although the difference was not statistically significant. 31…”
Section: Non-cultured Epidermal Cellular Graftsmentioning
confidence: 99%
“…However, there was no statistically significant difference in the repigmentation of leucotrichia or that of skin. This is because of the greater proportion of stem cells in the hair follicle niche 22 …”
Section: Donor Site Preparationmentioning
confidence: 99%